Households, governments, and corporations as economic actors : a pilot project on inequality in the circumpolar Arctic - Everett, Karen; Duhaime, Gérard (The Canada Research Chair on Comparative Aboriginal Condition, 2024)
This study is the pilot project for the WAGE Circumpolar Partnership, a SSHRC funded project, the objective of which is to better understand social and economic inequalities across the circumpolar Arctic. In particular, this research seeks to identify the income composition of households, governments, and corporations at the subnational level across the circumpolar region. The chapter on households identifies similarities and differences of income composition for individuals on a per capita basis. Data was collected from the national and regional accounts of the relevant national statistics agencies for five indicators: primary income, total transfers received, total income, total transfers paid, and disposable income in order to identify areas of income inequality. The data shows that, on average, individuals in the North American North earn the most income, followed by individuals residing in the northern Nordic regions and then in northern Russia, although there are variations within the regional blocs. For example, the average disposable income per capita for Greenland is closer to that found in Russia, while the average disposable income per capita in Yamal Nenets is similar to that in the Nordic regions. Moreover, the amount of transfers paid and received varies from one region to another and often plays an important role in reducing inequalities between regions within a country. Data for governments and corporations was harder to obtain. For governments, comparable data is not publicly available for all regions, meaning that a circumpolar comparison is not possible. For corporations, data at the regional level is also not available due to the tax location of many larger corporations and the need for such data to remain anonymous. The chapters on governments and corporations therefore suggest areas for future research. The disparities in data between the three actors/sectors constitute a challenge if we hope to achieve a fuller understanding of income composition and how this affects inequality. As such, ...